Health, Safety, And Enviroment (HSE), Budaya Perusahaan, Accident Terhadap Kinerja PT. Bakrie Autoparts Dimediasi Disiplin Kerja - Fadila Kurniasih; Dewi Puspaningtyas Faeni; Novita Wahyu Setyawati (PPIMAN Pusat Publikasi Ilmu Manajemen, 2024)
This study aims to determine Health, Safety and Enviroment (HSE), Corporate Culture, and Accident on the Performance of PT Bakrie Autoparts through (mediated) Work Discipline. This research method is descriptive quantitative type by distributing questionnaires (Likert scale 1-5) to a sample size of 83 out of 500 respondents calculated by the Slovin formula and processed with SmartPLS 3.0 software. The results showed that the path coefficient and p-value of the HSE variable (0.532 and 0.000), Corporate Culture (0.333 and 0.003), meaning that HSE, Corporate Culture affect the performance of PT. Bakrie Autoparts, as well as Accident on the path coefficient value and p-value (-0.029 and 0.790). This means that Accident has no effect on the performance of PT Bakrie Autoparts. Furthermore, the path coefficient and p-value of the Work Discipline variable is 2.491 and 0.013. This means that Work Discipline has a significant positive effect on the Performance of PT. Bakrie Autoparts.